Utility of mathematical knowledge as a motivating factor in students' learning of Adult Secondary Education - Donvito, Angel Eduardo (2019)
This paper analyzes the utility of the mathematics for Adult Secondary Education (ASE) as a factor to recover motivation in learning. The results of a survey with N=820 ASE students about their perspectives of the utility of mathematics are presented. The results show that teaching mathematics based on its inherent formative utility for daily life and work, could reduce much of adults’ difficulty to study mathematics. For mathematics to be useful for students, mental calculation and numerical operations should take an important place in the school curriculum. Mathematics problems should be developed in a similar way to those that adults face daily, regaining the arithmetic knowledge which adults master. The current way Algebra is taught should be reconsidered, students admit it is unhelpful, despite its potential. This phenomenon suggests a new research question: What type of school algebra should be taught in ASE?